2021
DOI: 10.1180/clm.2022.11
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of apparent sintering activation energy for densification of clays

Abstract: Clays are raw materials with properties that are necessary for the manufacture of ceramic tiles. The characteristics of clay ceramic raw materials may vary within the same mineral deposit. Clay blending promotes better use of clay reserves, thereby increasing the applicability and life cycle of raw materials. Therefore, it is important to understand the mechanisms controlling the firing of ceramic tiles. In this study, three different clays from a clay deposit were assessed and ten formulations were prepared u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…For water absorption ( Figure 6 c), Ag 2 O nanoparticles caused an increase up to 26% and 25% at 1% and 5% ( w / w ) to the 0% ( w / w ) mixture. This increase is caused by the appearance of a liquid phase that facilities porosity closure [ 71 ]. The addition of CuFe 2 O 4 nanoparticles resulted in a decrease in water absorption of up to 33% and 26% at 1% and 5% ( w / w ), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…For water absorption ( Figure 6 c), Ag 2 O nanoparticles caused an increase up to 26% and 25% at 1% and 5% ( w / w ) to the 0% ( w / w ) mixture. This increase is caused by the appearance of a liquid phase that facilities porosity closure [ 71 ]. The addition of CuFe 2 O 4 nanoparticles resulted in a decrease in water absorption of up to 33% and 26% at 1% and 5% ( w / w ), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the flexural strength of the tiles prepared in this work was significantly greater than those obtained from schist materials (156.15 kg cm –2 ; Kuru Mutlu & Mutlu, 2022). Thus, the material alternatives available to the tile industry can be expanded by developing such clay mixtures, which will reduce the energy costs of industrial processes (Comin et al , 2021).…”
Section: Resultsmentioning
confidence: 99%
“…According to Dondi [66], variation in drying shrinkage is "acceptable" or "optimal" The firing shrinkage behavior of the formulations showed that F2, with a high content of free silica, exhibited higher dimensional stability (less shrinkage) than that of samples F1 and F3. On the other hand, the presence of fluxing oxides (higher in F1 and F3), which enhance the formation of a liquid phase in the ceramic body and the densification of the piece, may cause an increase in shrinkage [65].…”
Section: Technological Characterization Of the Clays Compositionsmentioning
confidence: 99%